Developing Learning Motivation of Elementary School Students Through Discovery Learning Model - Rahman, Alma Firriyal; Husna, Nida’Ul; Rizqiani, Hanifah; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
The purpose of this study is to find out how the influence of the use of discovery learning model as a means of improving the learning motivation and learning outcomes of grade VI students in 03/20 Nambangan, North Rejowinangun, Central Magelang district, Magelang City in the era of the covid-19 pandemic. This study uses class action research (PTK). A class were selected in this study. Data collection are gathered from the students’ report book and postest through the use of discovery learning model. Based on the results of data analysis in cycle one with an average of 50 before the treatment while in cycle II there is an average increase of 100 after the treatment of the discovery learning model. It can be concluded that discovery learning model can increase students’ learning motivation and learning outcomes